Meningkatkan Kemampuan Mengenal Warna Melalui Eksperimen Hujan Pelangi - Fatma; Hidayatu Munawaroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Recognizing the concept of color is important for developing children's cognitive abilities. Color is a concept or indication that may appear as a result of the reflection of light or substances, and can also create an impression on the eye. Unfortunately, most children are still confused and don't even know what colors to use when coloring or when the teacher asks what color the object they are holding, the child just waits silently for the teacher to say it first and then the child follows. Apart from that, sometimes children feel bored when doing coloring activities, because coloring is usually the teacher's first step in introducing colors to children. This research uses a descriptive qualitative approach. The sample in this research were students at KB 'Aisyiyah Ulil Albab. This research aims to provide a new learning experience for students regarding color recognition. With this experimental activity, it is hoped that students will be able to improve their artistic and creative abilities.